Design, synthesis, and biological investigation of new thiazole-based derivatives as multi-targeted inhibitors endowed with antiproliferative, antioxidant, and antibacterial properties - Gomaa, Hesham A. M.; Atta, Asmaa M.; Shaker, Mohamed E.; Alzarea, Sami I.; Alsahli, Tariq G.; Alatwi, Eid; Musa, Arafa; Mohamed, Fatma A. M.; Alzahrani, Hayat Ali; Mohassab, Aliaa M.; Abdelmoez, Alshaimaa; Bräse, Stefan; et al. (Frontiers in Chemistry, 2025)
IntroductionA novel series of thiazole-based derivatives 11a-f and 12a-f was developed, synthesized, and tested for antiproliferative activity as dual EGFR/VEGFR-2 inhibitors, antioxidants, and antibacterial agents.MethodsThe structures of the new compounds 11a-f and 12a-f were validated using NMR spectroscopy and elemental microanalysis. The antiproliferative activity of 11a-f and 12a-f was tested against a panel of four cancer cell lines using MTT assay.Results and DiscussionCompounds 11d and 11f had the highest antiproliferative activity, with GI50 values of 30 and 27 nM, respectively, making them more potent than erlotinib (GI50 = 33 nM). Inhibitory studies for EGFR and VEGFR-2 demonstrated that compounds 11d and 11f were the most potent derivatives with dual inhibitory activity. Furthermore, compounds 11d and 11f exhibited significant antioxidant activity at 10 μM, with radical scavenging activity of 71% and 73%, respectively, compared to the reference Trolox (78%). Moreover, compounds 11a-f and 12a-f exhibit significant inhibitory activity against E. coli DNA gyrase, with compounds 11b, 11e, and 12b displaying the highest inhibitory efficacy, yielding IC50 values of 182, 190, and 197 nM, respectively, in comparison to the reference novobiocin (IC50 = 170 nM). Compounds 11b and 11e have significant antibacterial efficacy against both Gram-positive and Gram-negative bacterial strains, as demonstrated by a twofold serial dilution experiment. They exhibit similar efficacy against S. aureus, E. coli, and P. aeruginosa, demonstrating more potency than ciprofloxacin, however displaying reduced effectiveness against B. subtilis compared to ciprofloxacin.